Building technologies, local resources and empowerment:: A low cost housing project in East London, South Africa - D'ARAGON, Jean (ARCC Conference Repository, 2019)
The poverty and housing problems of the black, coloured and Indian communities of South Africa did not disappear with the end of the apartheid era. Besides a housing backlog of 1,5 million and a demand for 220 000 new houses every year, South Africans are suffering from underdevelopment at economic and social levels. This situation is not disconnected with the recrudescence of violence that is happening now in South Africa. Besides the persistence of the tensions between the different groups inherited from the former regime, the poor seem to be weary of waiting for a fairest redistribution of the wealth that is too slow to happen. Housing is only a part of the problems faced by developing countries. It should not be treated independently from the whole. The choice of a material, a technology is everything but innocent. It reflects political choices, values and cultures. In front of tremendous housing of developing countries, cost criteria often weight much in the balance. For that reason and in situation of emergency, project stakeholders often borrow models and technologies from overseas which are not suited to their new context. Beside not being adapted to the local climate and culture, these models often prevent the housing project to bring positive socio-economical impacts on the community. This paper is about a low cost housing project in East London, South Africa. Through the introduction of the compressed earth block technology, the project succeeded to reintroduce the use of a traditional material, and to bring it into urban areas. In maximising the use of local (material and human) resources, the project aimed to use housing to be a lever for local development and to bring positive socio-economical impacts on the community and the less possible negative impacts on the local and global environment. By modernising the use of a material that could be found almost anywhere in the world and that shelters more than a third of the humanity, the project succeeded to valorise earth as a noble local material, helping the communities to reduce their dependency on external materials, components and technology. The paper attempts to contribute to the development of local solutions to the universal housing problem rather than universal solutions to local housing problems. It also tries to present housing as a lever on which other local needs such as health, education and economy could find support to develop. It aims to propose economical solutions and building details that maximise the use of local (human and material) resources, that are simple enough to facilitate a technology transfer but not simplistic since it also wants to serve educational purposes. For these reasons, it tries to favour solutions that are respectful and correspond to the local know-how, and the cultural values of the communities that will benefit from such projects.